2020
DOI: 10.5664/jcsm.8778
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of insulin-like growth factor-1 as a biomarker of improved circadian rhythm sleep-wake disorder in school-aged children

Abstract: Study Objectives: We aimed to investigate whether improvements in the symptoms of circadian rhythm sleep-wake disorder after treatment were associated with an increase in serum insulin-like growth factor-1 (IGF-1) concentration. Methods: Eighty-seven school-aged children (32 males, 55 females), aged 14.31 ± 1.50 years (mean ± standard deviation), who were admitted to our hospital with circadian rhythm sleep-wake disorder received treatment for 6-8 weeks consisting of the following protocol: (1) lights-out for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Chennaoui et al also discovered that the IGF-1 system responds to sleep deprivation, with serum IGF-1 concentrations decreasing after 25 h of sleep deprivation and increasing again after a night of recovery (7). Kimura et al reported that decreases in the symptoms of patients with circadian rhythm sleep-wake disorders were associated with increased serum concentrations of IGF-1 (22). Although the results differ among those studies, they all suggest that sleep deprivation is related to IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Chennaoui et al also discovered that the IGF-1 system responds to sleep deprivation, with serum IGF-1 concentrations decreasing after 25 h of sleep deprivation and increasing again after a night of recovery (7). Kimura et al reported that decreases in the symptoms of patients with circadian rhythm sleep-wake disorders were associated with increased serum concentrations of IGF-1 (22). Although the results differ among those studies, they all suggest that sleep deprivation is related to IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma IGF-1 levels reveal a pronounced 24 h rhythm in rats with a peak level at the end of the dark phase and beginning of the light phase [ 113 ]. Inflammatory conditions could impair the IGF-1 rhythms [ 113 ], while improved circadian rhythm sleep–wake disorder is associated with increase in IGF-1 level [ 114 ]. Interestingly, melatonin is implicated in IGF-1 regulation via multiple pathways involved in the energy metabolism, e.g., PI3K–Akt signaling and glycogen synthase kinase 3 β (GSK3β) [reviewed in [ 100 ]].…”
Section: Interaction Of the Circadian System And Adult Neurogenesismentioning
confidence: 99%
“…The IIS pathway plays a vital role in sleep regulation. In the treatment of patients with circadian rhythm sleep-wake disorders, improvements in symptoms were found to be strongly associated with increased serum concentrations of insulin-like growth factor (IGF-1) [ 190 ]. In-depth studies have found that the activity of orexin neurons is modulated by IGF-1, which controls sleep duration and architecture [ 191 ].…”
Section: Does Tea Affect Sickness Sleep and Maintain Energy Homeostasis?mentioning
confidence: 99%